Análise microbiológica e caracterização eletroforética do queijo mussarela elaborado a partir de leite de búfala - Buzi, Kate Aparecida [UNESP]; Pinto, José Paes de Almeida Nogueira [UNESP]; Ramos, Paulo Roberto Rodrigues [UNESP]; Biondi, Germano Francisco [UNESP] (My University, 2009)
This study evaluated the microbiological quality of mozzarella cheese made from buffalo milk obtained from retail outlets and validated their authenticity by checking the product for the possible presence of cow milk. The microbiological analysis included counts of E. coli, total coliform, positive coagulase Staphylococcus, and Salmonella spp. For the determination of mozzarella purity, we used polyacrylamide gel electrophoresis. Based on the results of the microbiological evaluation, we can state that 98% of samples comply with the legal microbiological standards although some have shown high values of total coliforms, which indicates poor hygienic conditions during manufacturing. However, 2% of the samples showed fecal coliform populations exceed the legal limit due to high E. coli contamination. Electrophoresis detected cow milk in 22% of the samples, which was probably added intentionally.
Microbiological analysis and electrophoretic characterization of mozzarella cheese made from buffalo milk
Keywords: Adulterations; Buffalo; Electrophoresis; Microbiology; Mozzarella